LoRa-Based IoT Recommendations for Surabaya City Drainage Channel Using Multi-Node Multi-Hop Communication - Izzulhaq, Muhammad Arya; Widodo, Rusminto Tjatur; Oktavianto, Hary (Jurnal Rekayasa Elektrika, 2025)
This paper focuses on the development of a multi-hop LoRa (Long-Range) communication network for real-time monitoring of urban drainage Internet of Things (IoT), specifically simulating the flood-prone area along the drainage channel of Jalan Jawa, Surabaya City. The novelty of this research lies in the selection of the optimal communication environment through path loss and shadowing analysis prior to implementing a multi-node, multi-hop, sensor medium access control (S-MAC) method. The selected environment at the first location demonstrated a lower path loss exponent of 1.55, typical of "in-building line-of-sight," compared to the second location with a loss exponent of 2.82, which resembled "urban area cellular radio." Applying the multi-hop technique successfully extended the data transmission range up to 750 meters with nodes placed at 250 meter intervals while maintaining a high data transfer rate. The experiments showed that increasing distance significantly reduced the received signal strength indicator (RSSI), with values dropping from -52.75 dBm at 150 meters to -98.25 dBm at 750 meters. This paper demonstrates the feasibility of using multi-hop communication rather than the conventional multi-node technique to ensure reliable data transmission and wider range, offering a solid foundation for building a robust communication network in urban drainage monitoring systems.